Test reduction: I–Introduction and review of published work. Issue 6239 (23rd August 1980) - Card, W I; Emerson, P A
Abstract : The word "test" is used in a more general sense to describe the process of eliciting evidence of any kind from a patient, and this paper explores the thesis that much evidence is unnecessary and that therefore much test reduction is possible. The value of test reduction can be measured by its efficiency–that is, its effect on the misclassification of disease–or, preferably, by some measure of its cost-effectiveness.